Generalized Born–Infeld actions and projective cubic curves. Issue 3 (3rd February 2015) - Ferrara, S.; Porrati, M.; Sagnotti, A.; Stora, R.; Yeranyan, A.
Abstract : U(1) n supersymmetric Born‐Infeld Lagrangians with a second non‐linearly realized supersymmetry are investigated. The resulting non‐linear structure is more complex than the square root present in the standard Born‐Infeld action, and nonetheless the quadratic constraints determining these models can be solved exactly in all cases containing three vector multiplets.The corresponding models are classifed by cubic holomorphic prepotentials. Their symmetry structures are associated to projective cubic varieties. Abstract : We investigate U ( 1 ) n supersymmetric Born–Infeld Lagrangians with a second non–linearly realized supersymmetry. The resulting non–linear structure is more complex than the square root present in the standard Born–Infeld action, and nonetheless the quadratic constraints determining these models can be solved exactly in all cases containing three vector multiplets. The corresponding models are classified by cubic holomorphic prepotentials. Their symmetry structures are associated to projective cubic varieties.